The Influence of Casting Technology on the Mechanical Properties and Microstructure of the WE43 Alloy for Medical Applications - Białoń, J.; Sobczak-Kupiec, A. (Archives of Foundry Engineering, 2026)
Melting and casting technologies were developed for the aluminum-free magnesium alloy WE43, which is a promising candidate for biomedical applications due to its high biocompatibility. The alloy was melted in a steel crucible under a protective high-purity argon atmosphere at approximately 710°C to prevent oxidation. To evaluate the influence of the casting method on the final properties of the material, samples were prepared using three different technologies: from ingots, from castings produced by gravity casting into a steel mold, and from components obtained by high-pressure die-casting using a horizontal cold-chamber machine. The prepared samples were subjected to chemical composition analysis, non-destructive testing, mechanical characterization (hardness and tensile strength), and detailed microstructural evaluation using optical and electron microscopy. The results demonstrated that the alloy exhibited tensile strengths in the range of 100–200 MPa and porosity between 1.0–2.6%, while the microstructure was refined as a result of the applied casting techniques. The aim of this study was to identify the optimal production route to ensure the alloy's highest possible quality and performance of the alloy for biomedical use. Based on a comparative analysis of all the test results, the most suitable form and processing conditions of the WE43 alloy were determined for further development as the matrix material in an innovative, biodegradable magnesium-based biomaterial.